A synthesis of youth activation initiatives and their impact on tuberculosis knowledge, knowledge-seeking, and healthcare-seeking behavior in vulnerable populations - Ionescu, Ana-Maria; Mak, Joelle; Yan, Qu; Kumar, Nishant; Rao, Raghuram; Mattoo, Sanjay; Balasubramanian, Deepak; Acharya, Rachana; Quraishi, Subhi; Sharma, Niraj; Nurliyanti, Kep; Chin, Juliana; et al. (Frontiers in Tuberculosis, 2026)
BackgroundAnnually, up to 3 million people with tuberculosis (TB) fail to receive care due to delays in seeking TB care. Alongside active case finding, identifying cost-effective strategies that successfully mobilize vulnerable populations, such as young adults, to proactively present to care early is critical for ending the TB epidemic. Enabling populations to achieve optimized knowledge levels and proactively self-present to care may be more efficient than population-wide screening.MethodsBetween August 2021 and December 2023, five youth activation initiatives (“Be the Change”, MumbraTB-ACTS, and MTV Nishedh in India; TB Warriors in Indonesia; UVTB5+ in China) were implemented. Initiatives were assessed on reach and program engagement, TB knowledge improvement, knowledge-seeking behaviors, healthcare-seeking behaviors, TB volunteering, and TB self-screening, as precursors to presentation to care. Program outcomes measurements included number of individuals reached and knowledge change before and after implementation using knowledge, attitudes, and practices (KAP) surveys. Core healthcare-seeking behavior indicators were also tracked where feasible.ResultsAcross programs, various strategies were implemented to reach youth including social media, hybrid case-finding, mass media, gamification and peer education, and/or volunteer-driven health promotion. Variability in measurement and reporting of program outcomes confounded the synthesis of information across initiatives, but collectively the initiatives resulted in broad reach within each local context, resulting in more than 200 million youths reached and 100 million engaged. More than 800,000 individuals reported knowledge-seeking activities with >50,000 completed KAP surveys. Initiatives demonstrated evidence of empowering communities to proactively undertake screening and/or volunteer for TB initiatives. Three also measured positive improvements in knowledge of disease transmission, symptoms, and curability.ConclusionThese data highlight several locally successful strategies for increasing TB awareness and knowledge, and encouraging TB care seeking, as well as mobilizing youth to volunteer as community TB KAP advocates. Next steps to understanding the true impact of such activation TB initiatives should include the development of a global framework to provide guidance on best practices for impact assessment, particularly at the healthcare-seeking stage. This could support healthcare workers in their provision of equitable access to quality care and implementation of TB initiatives.